The Formation of the "Skillful Inaction" and "Aggressive Attack" Schools in the English Foreign Policy of the 19th Century - Oybek, Saydatov (European Journal of Life Safety and Stability (2660-9630), 2023)
There are problems in world history that have not lost their relevance and importance over the years. One of such problems is the Anglo-Russian rivalry in Asia, which began in the middle of the XIX century. This issue is reflected in the monographs of all major world historians, politicians and experts, as well as in many textbooks, magazines and newspaper articles on international relations and diplomacy. The process of struggle that began between the two imperialist states, Britain and Russia, has gathered many states around it over the years. This area of struggle has covered a very large area of the Eurasian region and has caused very complex political, economic and social problems. This article describes the formation of the schools of "skillful inaction", "forward policy" in English historiography, the first political figures of these schools and their views.